2015
DOI: 10.1016/j.tjog.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic trisomy 15 at amniocentesis: Prenatal diagnosis, molecular genetic analysis and literature review

Abstract: Prenatal diagnosis of mosaic trisomy 15 at amniocentesis should alert doctors about the occurrence of UPD 15 and a clinically significant phenotype. The present case provides evidence for cytogenetic discrepancy between uncultured and cultured amniocytes in mosaic trisomy 15 at amniocentesis. It is possible that the abnormal cell lines of amniocytes with trisomy 15 disappear after long-term cell culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…In our study, the percentages of cells for trisomy 21, 18 and 13 were in good agreement when DNA-based CNV-seq or CMA and cell-based chromosome analyses were compared. While mosaic trisomy 15 (Case 16 and Case 17), trisomy 8(Case 18), trisomy 2 (Case 22) and trisomy 22 (Case 19) were detected in the direct AF sample by CNV-Seq and CMA, however obviously lower levels of mosaicism was detected by karyotyping on cultured amniocytes which is consistent with the research reported previously [23][24][25][26]. It is feasible that the normal cells may have had a growth advantage in culture or the abnormal cell line may have a culturing disadvantage [13].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the percentages of cells for trisomy 21, 18 and 13 were in good agreement when DNA-based CNV-seq or CMA and cell-based chromosome analyses were compared. While mosaic trisomy 15 (Case 16 and Case 17), trisomy 8(Case 18), trisomy 2 (Case 22) and trisomy 22 (Case 19) were detected in the direct AF sample by CNV-Seq and CMA, however obviously lower levels of mosaicism was detected by karyotyping on cultured amniocytes which is consistent with the research reported previously [23][24][25][26]. It is feasible that the normal cells may have had a growth advantage in culture or the abnormal cell line may have a culturing disadvantage [13].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the percentages of cells for trisomy 21, 18 and 13 by cell-based chromosome analyses were in good agreement with mosaicism levels measured by DNAbased CNV-seq or CMA and were compared. However, for mosaic trisomy 15, trisomy, trisomy 2 and trisomy 22, levels of mosaicism by CNV-Seq and CMA were higher than those seen by karyotyping, which is consistent with previous reports for autosomal mosaicism [27][28][29][30]. This supports the general notion that normal cells may have had a growth advantage in culture or the abnormal cell line may have a culture disadvantage [18].…”
Section: Discussionsupporting
confidence: 90%
“…For cases 23,26,27,30,32 and 61, both CNV-seq and CMA showed a normal result in uncultured amniotic fluid cells, but karyotyping showed a mosaic pattern of monosomy X or disomy X in cultured amniotic fluid cells. Among these cases, karyotyping detected a mosaic pattern of monosomy X or disomy X of less than 10% in 5 of the 6 cases.…”
Section: Chromosomal Mosaicism For Sex Chromosome Aneuploidymentioning
confidence: 91%
“…These results are consistent with those reported in the literature (Table 2). [16][17][18][19][20][21] Chen et al 22,23 reported that the calculated level of trisomy mosaicism in amniocytes was higher from fluorescent in situ hybridization (FISH) analysis (using uncultured amniocytes) compared with karyotype analysis. As mentioned above, these results may reflect the poor genetic stability and elimination of cells with trisomy during long-term cell culture (required for karyotype analysis), leading to the relatively reduced levels of trisomy mosaicism from karyotype analysis.…”
Section: Discussionmentioning
confidence: 99%